Dynamics of psychophysiological characteristics of highly qualified combat athletes after hypoxic stimulation - Tambovtseva, R. V.; Sechin, D. I. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to test stability of sensory and motor functions in highly qualified combat athletes after hypoxic stimulation. Methods and structure of the study. The experiment ran at the Muscular Activity Bioenergy Laboratory of the N.I. Volkov Sports Biochemistry and Bioenergy Department. Sampled for the experiment were 15 athletes aged 20 to 25 years. The study was conducted according to the standard laboratory program using psychophysiological and hypoxic tests. Results of the study. The study found a pronounced ergogenic effect of hypoxic stimulation on the psychomotor system of athletes, associated primarily with the sport-specific peculiarities of the training and competitive activities and presence of chokeholds. Conclusion. Based on the analysis of the table values, it was concluded that there were no pronounced negative changes in all the psychophysiological indicators under study. Despite increased fatigue of the visual analyzer resulting from hypoxic stimulation, there was a decrease in the reaction time and in the number of errors made when completing the tasks related to mental activity.